2010
DOI: 10.3138/cmlr.66.5.639
|View full text |Cite
|
Sign up to set email alerts
|

Pratiques de littératie à l'école. Pour une approche ethnographique de la classe en deuxième année d'immersion en Colombie-Britannique

Abstract: Pratiques de littératie à l'école. Pour une approche ethnographique de la classe en deuxième année d'immersion en Colombie-Britannique Danièle Moore Cécile Sabatier Résumé : À partir d'un corpus recueilli dans trois classes de deuxième année de l'école primaire en immersion française en Colombie-Britannique, l'article explore le concept de littératie(s) dans son articulation avec les notions de contexte et de culture éducative, et présente la méthodologie et les classes observées selon une perspective ethnogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Existing research and comparison of English language arts and CF curriculum documents suggest that the strategies observed here highlight the potential for reciprocity of support for the development of literacy skills across subject-specific classrooms. Like the teachers in Moore and Sabatier's (2010) study, Christine's observed practices seemed to be greatly influenced by her belief in the interdependence of day-today literacy skills (as supported by Cummins, 1979Cummins, , 2001. She acknowledged that her students were coming into her CF class with existing L1 literacy skills, and findings demonstrated that she explicitly attempted to capitalize on this in her CF teaching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research and comparison of English language arts and CF curriculum documents suggest that the strategies observed here highlight the potential for reciprocity of support for the development of literacy skills across subject-specific classrooms. Like the teachers in Moore and Sabatier's (2010) study, Christine's observed practices seemed to be greatly influenced by her belief in the interdependence of day-today literacy skills (as supported by Cummins, 1979Cummins, , 2001. She acknowledged that her students were coming into her CF class with existing L1 literacy skills, and findings demonstrated that she explicitly attempted to capitalize on this in her CF teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Findings showed that structured instructional scaffolding and emphasis on the role that literacy plays in the development of oral skills emerged as key elements in participating teachers' ideas and practices of what effective literacy instruction entails. Moore and Sabatier (2010) also investigated how three primary FI teachers conceptualized literacy instruction in their classrooms. The range of observed student modalities and instructional strategies led the authors to suggest that teachers' practices were greatly influenced by their belief in the interdependence of dayto-day literacy skills.…”
Section: Literacy Teaching In Fsl Contexts In Canadamentioning
confidence: 99%
“…L'espace physique de la salle de classe participe à inscrire la construction des compétences et des savoirs littératiés dans la spécificité des classes dans lesquelles elle est observée (Moore et Sabatier, 2010 Les dimensions plurilittératiées des ouvrages, telles que nous les avons rapidement mises à jour dans les quelques exemples de livres bi/plurilingues rencontrés dans les coins bibliothèques des classes, conduisent à apporter des éléments de réflexion pour développer dans le contexte scolaire qui est le nôtre, le rapport à la littératie en français sur un mode bi-/plurilingue dans la mesure où le rapport au français et à la langue écrite se construit naturellement en contact avec d'autres univers linguistiques, culturels et symboliques.…”
Section: Des Espaces Et Des Livres Bi-/plurilinguesunclassified